No-fault compensation for medical injury: the New Zealand experience - Jahn Kassim, Puteri Nemie (International Islamic University Malaysia, 2003)
The deficiencies of the tort system in handling medical negligence claims have been apparent for a number of years. The inaccessibility of the litigation system and particular difficulties of proving medical negligence deter many potential litigants from pursuing their claim. Alternatives to the fault-based system have been proposed and also implemented in some countries such as New Zealand, Sweden and Finland. These countries have adopted no-fault compensation schemes to compensate victims of medical injuries. By implementing a no-fault compensation scheme, fault becomes irrelevant, as a social insurance plan provides compensation for all personal injuries arising out of accidents, including medical mishaps, whatever may have been their cause. New Zealand was the first country to adopt a comprehensive no-fault compensation scheme for personal injury by accident. The scheme covered work and road traffic accidents, those occuring at home or during sporting activity and also, the results of medical mishaps and malpractices. The scheme's workings and development have been a source of interest for policy makers to obtain important information on how to overcome the rigours of the fault-based system. The New Zealand scheme can provide valuable lessons for a country in designing a no-fault scheme for medical injuries which is simple to run, straight forward in operation and acceptable in costs.